2022
DOI: 10.1007/s00704-021-03892-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the response of the Botswana High to El Niño Southern Oscillation using a variable resolution global climate model

Abstract: The Botswana High is an important component of the regional atmospheric circulation during austral spring, summer and autumn. While the high tends to be stronger during El Niño and weaker during La Niña, its direct response to El Niño Southern Oscillation (ENSO) remains unknown. To that end, a variable resolution global climate model (Model Prediction Across Scales version 7, hereafter MPAS) is applied with relatively high resolution (48 km grid spacing) over southern Africa and a coarser resolution (240 km gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Drought years calculated from the Riverview-SPI, which typically coincide with El Nino events while wet years coincide with La Nina events in the Hlabisa subdistrict, are consistent with previous studies which found similar results over the Southern African region (Gore et al 2020 ; Maoyi and Abiodun 2021 , 2022 ). That is because El Nino years are characterised by anomalous upper tropospheric convergence (at 200 hPa) over the Southern African domain leading to increased subsidence and drought conditions, while La Nina years were characterised by anomalous upper tropospheric divergence (at 200 hPa) which may lead to enhanced convection and increased rainfall over the region (Maoyi and Abiodun 2021 , 2022 ). The years 2014, 2015 and 2016 were particularly dry years in Hlabisa, as demonstrated by the SPI.…”
Section: Discussionsupporting
confidence: 91%
“…Drought years calculated from the Riverview-SPI, which typically coincide with El Nino events while wet years coincide with La Nina events in the Hlabisa subdistrict, are consistent with previous studies which found similar results over the Southern African region (Gore et al 2020 ; Maoyi and Abiodun 2021 , 2022 ). That is because El Nino years are characterised by anomalous upper tropospheric convergence (at 200 hPa) over the Southern African domain leading to increased subsidence and drought conditions, while La Nina years were characterised by anomalous upper tropospheric divergence (at 200 hPa) which may lead to enhanced convection and increased rainfall over the region (Maoyi and Abiodun 2021 , 2022 ). The years 2014, 2015 and 2016 were particularly dry years in Hlabisa, as demonstrated by the SPI.…”
Section: Discussionsupporting
confidence: 91%
“…Mapping climate parameters using advanced cartographic methods is presently the subject of intense research. Approaches to image processing [1,2], climate data modelling [3] and landscape studies [4] have largely converged on the requirements for the importance of cartographic visualisation for a proper environmental analysis for feature extraction and evaluation. While standard methods of handling spatial data such as Geographic Information Systems (GIS) are popular for climate and environmental mapping [5][6][7], superior performance has been demonstrated by incorporating advanced scripting solutions for complex cartographic tasks.…”
Section: Introductionmentioning
confidence: 99%